Factors Affecting the Profitability of Banks: A Field Study of Banks Operating in Jordan - Al-abedallat, Abedalfattah Zuhair (European Scientific Journal, ESJ, 2017)
Profitability is one of the most important objectives of the banks. It is an evidence of the efficiency of its management and its ability to attract money and investments. The study aimed at investigating the impact of a combination of factors (Assets, Direct credit Facilities, Deposits, Owner’s equity, Branches, and Automated Teller Machines (ATMs) on the profitability of banks in Jordan as measured by â€œReturn on Assetsâ€ and â€œReturn on Owners’ equity.â€ The study used the Eviews program to answer questions about the study and test the hypotheses. The tool for the study was the data variables of the study for the operating banks in Jordan that were collected from the annual financial statement of the Jordanian Central Bank and Association of Banks in Jordan for the period of 2000 to 2015. The study found that there is a significant statistical impact of the factors (Assets, Direct credit Facilities, Deposits, Owner’s equity, Branches, ATM) together on the return on assets (ROA). Also, there is a significant statistical impact of the factors (Assets, Direct credit Facilities, Deposits, Owner’s equity, Branches, ATM) together on the return on Ownersâ€™ equity (ROE). It also recommended that the Banks in Jordan should increase diversification in the investment to increase profitability. In addition, this study pointed the need for banks to expand in electronic banking services in order to increase profits and reduce costs.